The Effect of Rating Agencies on Herd Behaviour - Giovanni Ferri; Andrea Morone (Economics and Econometrics Research Institute (EERI), 2008)
This paper purports to provide some evidence on the effect of rating agencies on herding in financial markets. By means of a laboratory experiment, we investigate the effect and interaction between private and public information. Previous experiments showed that lemmings behaviour can survive in a market context where information is private (Hey and Morone, 2004), and that an experimental market can be very volatile and not efficient in transmitting information (Alfarano et al., 2006). We study experimentally, if socially undesirable behaviour – that survives in a market contest – may be eliminated owing to the presence of rating agencies.
Keywords: C91; D82; D83; 330; Herd behaviour; informational cascades; rating agency; bubble